PENGARUH METODE DISKUSI TERHADAP MINAT BELAJAR SISWA DALAM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Amalia Nurjannah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2021)
The purpose of this study to determine the effect of use of the discussion method on the student's learning interest in learning in the SKI. The research method used was quantitative method using the ex-post facto design.The subject of this research were 25 student of grade VIII B2 SMP IT Raudhatul Ulum. Hypothesis testing with simple linier regression. The result of the research shows that there is a significant influence of the use of the discussion method on the student’s learning interest in learning in the SKI in SMP IT Raudhatul Ulum.